Zika virus disease : from origin to outbreak - Qureshi, Adnan I. (Academic Press, 2018)
Zika Virus provides an authoritative account of one of most fascinating viruses of the 21st century, covering all the main points. It includes coverage of clinical manifestations, such as fever and fatigue, but also delves into neurological manifestations like acute demyelinating neuropathy. In addition, the book discusses new evidence that suggests that Zika fever in pregnant women can cause abnormal brain development in fetuses by mother-to-child transmission. The Zika virus infection has become one of the first where women are actively discouraged from getting pregnant. Readers will find this book to be a comprehensive resource on the topic.